The (Dis)order of Politics: τὸν δῆμον πράττειν ὃ ἂν βούληται. The Athenian Assembly and the Arginusae Trial (Circe de clásicos y modernos, 2025)
During the fifth century BC, the people’s role in the Athenian assembly took on a unique dynamic that provoked criticism from many ancient authors. In the period surrounding the oligarchic coups of 411 and 404, certain aspects of this dynamic also seem to have been exacerbated. In this context, the trial in 406 of the generals of the Arginusae battle constitutes an event of great relevance for understanding how popular sovereignty operated in the meetings held on the hill of Pnyx and what were the political, institutional, and subjective effects of this collective functioning.
Keywords: Athens; democracy; assembly; Arginusae; trial